A GLOBAL ASSESSMENT OF THE IMPLEMENTATION LEVELS OF THE EDUCATION FOR ALL (EFA) INITIATIVE AND THE MILLENNIUM DEVELOPMENT GOALS (MDGs) ON EDUCATION IN SUB-SAHARAN AFRICA: A FOCUS ON NIGERIA - Musa, C. N.; Agbaire, Jennifer J. (Sokoto Educational Review, 2013)
This paper presents an analytical appraisal of the varying levels to which the Education for All (EFA) project linked with two of the Millennium Development Goals (MDGs) has been implemented in sub-Saharan Africa with particular focus on Nigeria. It draws attention to the inequities among countries of the region while generally assessing Nigeria’s prospects in the achievement o f the EFA goals. The paper begins by highlighting the goals of the EFA project which include expanding and improving comprehensive early childhood care and education, especially for the most vulnerable and disadvantaged children and the educational MDGs by 2015 and the MDGs while aligning them with Nigeria’s policies on education. It then proceeds to examine advances made in implementing EFA goals such as the expansion of Early Childhood Care and Education and challenges in Nigeria and sub-Saharan Africa. Finally, practical strategies, geared at improving the achievement potential of the region in general and the country, in particular, are recommended. To this end, making practical plans to fund and manage all levels of education so that they can be accessible to all children regardless of socio-economic background and location was strongly advocated.